A Study to Assess the Feasibility of Implementing a Web‐Based Decision Aid for Birth after Cesarean to Increase Opportunities for Shared Decision Making in Ethnically Diverse Settings. (18th October 2018) - Shorten, Allison; Shorten, Brett; Fagerlin, Angela; Illuzzi, Jessica; Kennedy, Holly Powell; Pettker, Christian; Raju, Dheeraj; Whittemore, Robin
Abstract : Introduction: Decision aids are central to shared decision making and are recommended for value‐sensitive pregnancy decisions, such as birth after cesarean. However, effective strategies for widespread decision aid implementation, with interactive web‐based platforms, are lacking. This study tested the feasibility and acceptability of implementing a Health Insurance Portability and Accountability Act‐secure, web‐based decision aid to support shared decision making about birth choices after cesarean, within urban, ethnically diverse outpatient settings. Methods: A before‐and‐after design was used to assess feasibility and acceptability for decision aid implementation. Measures included women's knowledge, decisional conflict, birth preferences, birth outcomes, decision aid use, decision aid acceptability ratings (content, features, and functions), and views on how the decision aid supported shared decision making. Results: Of the 68 women who participated, most were black (46.2%) or Hispanic (35.4%). Their knowledge scores increased by 2.58 points out of 15 ( P < .001; d = 0.87), and decisional conflict score reduced by 0.45 points out of 5 points ( P < .001; d = 0.69). Forty‐four women (65.9%) attempted a vaginal birth after cesarean, of whom 29 (65.7%) succeeded. Women rated decision aid content, features, and functions as good or excellent. Most indicated they would recommend it to others. Health care providers recommended additional strategies to simplify decision aid access and integration into routine care. Discussion: Implementing web‐based decision aids within ethnically diverse practice settings is potentially feasible and worthwhile. However, strategies are needed to improve women's access and to encourage timely decision aid usage to prepare them for decision discussions with health care providers. Sustained implementation will require seamless integration into clinic workflow, which could include health care provider tools (counselling guides) embedded within the electronic health record, along with continuing education to support and engage health care providers in their use.